The Role of US Contrast Agents in US-Guided Biopsy of Focal Liver Lesions: A Pictorial Review - Lorentzen, Torben; Nolsoe, Christian Pallson (Ultrasound International Open, 2019)
US-guided percutaneous biopsy of focal liver lesions (FLL) is a classic interventional procedure performed by almost all radiology units. Typically, an incidental focal finding on US or a focal indeterminate lesion diagnosed on CT, MRI or PET/CT is referred for US-guided biopsy for final diagnosis. The introduction of microbubble US contrast agents has overcome some of the limitations of standard US in diagnosing FLLs by displaying the microvasculature together with the US morphology, which has increased both the sensitivity and the specificity. The combination of CEUS and intervention is facilitated by newer US equipment providing split-screen mode, which displays the CEUS mode alongside the standard US mode simultaneously on a single monitor. The puncture line is displayed in both modes as well as on the monitor. The interventional device (i. e., biopsy needle) is typically best visualized in the standard US mode, while the characteristic tissue pattern in an FLL is typically best visualized in CEUS mode. There are 3 main categories in which CEUS has an impact on US-guided biopsy of FLLs: • CEUS improves the visualization of FLLs • CEUS improves the quality of the biopsy specimen from an FLL • CEUS reduces the need for US-guided biopsy of an FLL In the two first categories, CEUS is utilized simultaneously with US-guided biopsy to ensure correct needle targeting. In the last category, US-guided biopsy of the FLL becomes superfluous as a result of the CEUS examination.
Keywords: contrast agents; ultrasound; biopsy; tumor